The Effectiveness of Interpersonal Communication in the Sultan Iskandar Muda High School Educational Institution (International Journal of Cultural and Social Science, 2023)
Basically humans are born as individual beings who are not separate, not divided between their soul and body. Human development as an individual being does not only mean the unity of body and soul. Humans have characteristics with their own personality patterns. This difference teaches that humans cannot live without other humans. The peace that we feel is born from good communication. Therefore, inheriting skills in communication and ethics needs an education that becomes a vehicle for learning for generations of the nation.